S+(S-22)=S+46

Simple and best practice solution for S+(S-22)=S+46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for S+(S-22)=S+46 equation:


Simplifying
S + (S + -22) = S + 46

Reorder the terms:
S + (-22 + S) = S + 46

Remove parenthesis around (-22 + S)
S + -22 + S = S + 46

Reorder the terms:
-22 + S + S = S + 46

Combine like terms: S + S = 2S
-22 + 2S = S + 46

Reorder the terms:
-22 + 2S = 46 + S

Solving
-22 + 2S = 46 + S

Solving for variable 'S'.

Move all terms containing S to the left, all other terms to the right.

Add '-1S' to each side of the equation.
-22 + 2S + -1S = 46 + S + -1S

Combine like terms: 2S + -1S = 1S
-22 + 1S = 46 + S + -1S

Combine like terms: S + -1S = 0
-22 + 1S = 46 + 0
-22 + 1S = 46

Add '22' to each side of the equation.
-22 + 22 + 1S = 46 + 22

Combine like terms: -22 + 22 = 0
0 + 1S = 46 + 22
1S = 46 + 22

Combine like terms: 46 + 22 = 68
1S = 68

Divide each side by '1'.
S = 68

Simplifying
S = 68

See similar equations:

| 8.6x+1.3x=9.9 | | y=0.43x+33 | | 2.4x-0.4x=68 | | y=0.43+33 | | 8.75+9=12.5t+12 | | 3-(x-2)=4 | | 4r-6= | | 6/90=x/75 | | (3x+70)=x | | X+3-11x=x+5-7x-16 | | 5b+2(4b+3)=-59 | | 4x^4-x^3-3x^2+9x-10=0 | | 2x+75+52y+1=180 | | 3x=x+2+10 | | 15+47.45x=49.95x | | 2g+10=7g | | 6x+4x+3+7=5x+3+4x | | 9.5z=-161.5 | | 3x+12=-5x-60 | | (9x-15)^(1/2)=(7x-5)^(1/2) | | -3y+-y= | | 9.5z=161.5 | | 88-117=-6(-4y)-13(2y)+y | | y=6(x-4)2-7 | | 11x-0=16 | | -4n+9n-6=-58 | | 7y/6-1/6 | | -6x*3/4 | | 3/10m=25 | | 0.5n+0.5n+n=180 | | (3*x)+(3*8)=42 | | 2x-(x-2)=11 |

Equations solver categories